Learning and Teaching in Hotel Management Studies : Defining the Students ’ Experience - Liasidou, Sotiroula (My University, 2016)
Studies in hotel management can be divided into two broad areas: the first is theory and the second is practice. Theory is discussed during lectures and practice takes place in the areas where the industry exists. The aim of this paper is to present the various methods of learning and teaching with emphasis on the way the students define and perceive various experiences during studying. The 4Es model of Pine and Gilmore (1999) is taken into consideration for the categorisation of the students’ experiences during studying. The method used is qualitative and in particular focus groups with the final sample to be 100 students studying Hotel Management in Cyprus. The results revealed the incorporation of various methods of students interrelated their experiences with the personality and style of the educator, the notes content along with extra curricula activities, industrial placement and the cohort of their classmates in each class.
Keywords: tourism studies; experiential realms; teaching; learning; hotel management studies